Determination of Green Human Resource Management: Analysis of Green Knowledge Sharing Green Competitive Advantage Green Training Green Psychological Climate and Green Innovation - Syahridhan, Sayed; Susanto, Primadi Candra (Journal of Management World, 2025)
The purpose of this literature research is expected to help hypotheses for future authors in determining research related to green human resource management. The research article Determining Green Human Resource Management: analysis of Green Knowledge Sharing, Green Competitive Advantage, green training, Green Psychological Climate, and Green Innovation is a scientific literature article on the scope of human resource management. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct literature reviews of relevant previous articles. The data used in this study are secondary data, which are sourced from academic online media such as Thomson Reuters Journals, Sage, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Green Knowledge Sharing affects Green Human Resource Management; 2) Green Competitive Advantage affects Green Human Resource Management; 3) Green Training affects Green Human Resource Management; 4) Green Psychological Climate affects Green Human Resource Management; and 5) Green Innovation affects Green Human Resource Management.